THE PERFORMANCE OF EXTRACTION EQUIPMENT MODIFICATION TOWARD SIZE PARTICLE OF TUBER AND YIELD OF INULIN OF DAHLIA FLOWER TUBER (Jurnal Bahan Alam Terbarukan, 2017)
Isolation of inulin from starch generally is done by extraction method. The size of the material to be extracted will affect the extraction process performance. In laboratory scale, the size reduction was done with a knife and the separation of starch from tubers was done by juicer. Temperature fluctuations during the extraction process would affect the yield of inulin, hence juicers and waterbath were found ineffective for larger scale. This research was aimed to design an extractor equipped with agitator blades for size reduction and a temperature controller. Extractor performance was investigated by evaluating agitation time (60-150 minutes), distance between agitator blades on the shaft (5 and 7 cm), number of the agitators, (1, 2, and 3 blades) against the fineness of cut material, starch and inulin content.  The results showed that the highest fineness of the samples was achieved at a distance of agitator blade of 7 cm, with 3 agitator blades and agitating time of 150 minutes. The highest yield of starch was 11.7% at size reduction time of 120 and 150 minutes using 3-blades agitator and the distance of 7 cm. The content of crude inulin obtained were by using the extractor was 2.206% and 2.213% by using the water bath. The difference of inulin content was 0.007% so it suggests that the extractor designed in this study can be used on inulin production in larger scale. The efficiency of the extractor was 85%.